Rac1, A Potential Target for Tumor Therapy - Liang, Jiaxin; Oyang, Linda; Rao, Shan; Han, Yaqian; Luo, Xia; Yi, Pin; Lin, Jinguan; Xia, Longzheng; Hu, Jiaqi; Tan, Shiming; Tang, Lu; Pan, Qing; et al. (Frontiers in Oncology, 2021)
Rac1 is one of the important members of Rho GTPases. It is well known that Rac1 is a cytoskeleton regulation protein that regulates cell adhesion, morphology, and movement. Rac1 is highly expressed in different types of tumors, associated with poor prognosis. Studies have shown that Rac1 participates not only in the tumor cell cycle, cell apoptosis, proliferation, invasion, migration, and angiogenesis, but also in the regulation of tumor cell stemness, thereby promoting tumorigenesis. In addition, Rac1 also plays a key role in anti-tumor therapy and participates in immune escape mediated by the tumor microenvironment. Research has also shown that the Rac1 inhibitor has good prospects in tumor prevention and treatment. Therefore, Rac1 is considered as a potential target for the prevention and treatment of tumors. The necessity and importance of Rac1 are obvious, but it still needs further study.